2015
DOI: 10.1080/10967494.2015.1012574
|View full text |Cite
|
Sign up to set email alerts
|

Putting Public Policy Defaults to the Test: The Case of Organ Donor Registration

Abstract: service reform, democratic renewal and governance in a comparative context and he has published extensively on these subjects and more broadly on theory and methods within political science. AbstractThere is growing interest within public management in using governance tools to influence citizens' behaviour, including changing 'choice architecture' by manipulating defaults. This paper reports a survey experiment with 4005 British adults which examined the impact of different defaults on people's propensity to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 38 publications
0
18
0
1
Order By: Relevance
“…Our analysis also unveiled studies that not only deal with cognitive biases in behaviors and judgments but also incorporate key tenets of nudging theory. These studies cover a variety of public decision domains, including improving attitudes toward government trustworthiness (Grimmelikhuijsen and Meijer 2012), increasing the collection of delinquent fines (Haynes et al 2013), boosting organ donations (Moseley and Stoker 2015), reducing the likelihood that home buyers become delinquent or default on their mortgages (Moulton et al 2015), and encouraging the adoption of desired health behaviors (Vlaev et al 2016).…”
Section: Resultsmentioning
confidence: 99%
“…Our analysis also unveiled studies that not only deal with cognitive biases in behaviors and judgments but also incorporate key tenets of nudging theory. These studies cover a variety of public decision domains, including improving attitudes toward government trustworthiness (Grimmelikhuijsen and Meijer 2012), increasing the collection of delinquent fines (Haynes et al 2013), boosting organ donations (Moseley and Stoker 2015), reducing the likelihood that home buyers become delinquent or default on their mortgages (Moulton et al 2015), and encouraging the adoption of desired health behaviors (Vlaev et al 2016).…”
Section: Resultsmentioning
confidence: 99%
“…It has been shown that, on average, changing the default to an opt-out system leads to an increase in donation rates (Bilgel, 2012;Johnson & Goldstein, 2003;Rithalia, Myers & Snowden, 2009;Ugur, 2015) and this change is supported by public opinion (Moseley & Stoker, 2015;Rockloff & Hanley, 2014;van Dalen & Henkens, 2014). However, while, on average, opt-out is associated with higher deceased donations, compared to opt-in, it is also associated with lower living donations (Shepherd, O'Carroll & Ferguson, 2014).…”
Section: Organ Donationmentioning
confidence: 99%
“…Samples can be gathered in a number of ways, either in person by researchers in field settings (James and Moseley 2014), using Internet panels (Moseley and Stoker 2015), or using other online recruitment tools such as MTurk, where participants are paid a nominal amount to complete a survey (Marvel 2015). They can also be administered directly to citizens by post or phone, using postal lists or telephone directories to identify participants (e.g., James 2011).…”
Section: Sampling Issuesmentioning
confidence: 99%